SURVEY AT BAT ENTEROPARASITES BY CENTRIFUGAL FLOTATION TECHNIQUE (MAMMALIA: CHIROPTERA) IN THE TROPICAL FOREST OF BRAZIL - da Costa Pinheiro, Michele (2013)
The frequency of intestinal parasites was established in 5 species of bats of the family Phyllostomidae captured in three different areas of study, located in the Village of Tinguá located in the far northeast of the city of Nova Iguaçu and the southern limits Tinguá Biological Reserve, in the State of Rio de Janeiro, Brazil in April and July 2012. Each fecal sample was individually analyzed and processed by a modified centrifugal flotation procedure in sucrose solution. No eggs or cysts of endoparasites were detected in the 33 samples analyzed. This is the first study of the fauna endoparasites in bats using centrifugal flotation technique using only fecal samples. All surveys are based on necropsy of examined hosts.